Effects of mineral supplementation on growing cattle and in vitro fermentation by ruminal microbes - Katulski, Savannah Lee (Kansas State University, 2017)
Three studies were conducted to assess effects of mineral supplementation on growing cattle performance, mineral status, and in vitro fermentation. Exp. 1 was a 3-part study that measured effects of Cu source and concentration on in vitro fermentation by mixed ruminal microbes. An initial in vitro experiment was performed to identify a Cu concentration (0, 100, 200, 300, 400, or 500 mg Cu/kg substrate DM) that would yield a 50% decrease in gas production. This concentration (100 mg Cu/kg substrate) was then used to evaluate varying Cu sources in the 3rd part of Exp.1. Titration of Cu (0, 10, 20, 30, 40, 50, 60, and 70 mg Cu/kg DM substrate) linearly decreased (P < 0.01) in vitro gas production, acetate, and propionate production. Inhibition of ruminal fermentation by Cu sources (CuSO₄, CuCl₂, CuCO₃, CuO, and tribasic copper chloride) also was evaluated using an in vitro fermentation system. Sources were incorporated into cultures at 100 mg Cu/kg substrate DM, a concentration great enough to elicit an inhibitory response. Copper sulfate and CuCl₂ were more inhibitory to in vitro fermentation, as indicated by decreases in gas production, VFA, and IVDMD, and increases in pH (P < 0.01). In Exp. 2, heifers were fed 3 different free-choice minerals: salt (S), a dry mineral basemix with salt (M), and a cooked molasses block (B); M and utilized the identical basemix. Mineral source had no effect on DMI, G:F, or concentrations of plasma P and Zn (P > 0.10). Average daily gain was greatest for M (P = 0.03), and not different between S and B (P = 0.98). Liver Cu concentrations were different among treatments (P < 0.01), with M having the greatest, B intermediate, and S having the least. Total dietary mineral intake also was different among treatments (P < 0.01), and was greatest for M, intermediate for B, and the least for S (P < 0.01). Experiment 3 × 4 factorial design and evaluated minerals added as different supplement types and trace mineral concentrations (0, 1, 5, or 10×) in an in vitro batch culture fermentation. Cooked molasses mineral blocks were compared to a dry mineral premix, and a dry mineral premix + molasses block added separately. In vitro fermentation was not different between the two molasses block treatments (P > 0.01); however, addition of molasses blocks increased fermentation to a greater extent than dry mineral alone (P < 0.01). Increasing trace mineral concentration decreased fermentation linearly (P < 0.01). In conclusion, excesses of trace elements can adversely affect fermentation by ruminal microbes. Mineral status in growing cattle was reflective of mineral intake; however, block supplements may be a method to control mineral intake to minimize overconsumption.
Keywords: Supplementation; Cattle; Performance; Microbial; FermentationMineral